Voltammetric determination of paracetamol in drugs using an electrode modified by poly(3,4-ethylendioxythiophene) film with a gold deposit - L.G. Shaidarova; A.V. Gedmina; I.E. Rogozhin; I.A. Chelnokova; H.C. Budnikov (Учёные записки Казанского университета: Серия Естественные науки)
A composite film of poly-3,4-ethylenedioxythiophene (PEDOT) with a gold deposit (Au-PEDOT-GCE) on the surface of a glassy carbon electrode (GCE) shows electrocatalytic activity in the oxidation of paracetamol. Working conditions for the immobilization of the Au-PEDOT composite on the GCE were determined. A method for the voltammetric determination of paracetamol on Au-PEDOT-GCE was proposed. It was revealed that the dependence of the oxidation current of paracetamol on its concentration is linear in the range from 1·10–7 to 1·10–3 mol·L–1. The developed voltammetric method was tested to determine paracetamol in drugs.